Aksi Daur Ulang Sampah Plastik Oleh Anak Sekolah Minggu GKPI Dame DR. I.L. Nommensen Resort Sainihuta Sebagai Wujud Kepedulian Terhadap Ciptaan Tuhan - Rani Letare Tobing; Gracie Arrabella Nainggolan; Laudia Ananta Sopya Br Bangun; Nurika Bunga Amelia Sianturi; April Yanti Lestari Lase; Naema Ananta Hutagalung; Yulia K. S. Sitepu (Indo Publishing, 2025)
The environment is part of God's creation that needs to be protected and preserved by humans. The church plays a crucial role in instilling environmental values ​​as part of their faith-based responsibilities, including in Sunday School children. This study aims to determine how environmental education and practices can foster environmental awareness among Sunday School children from an eco-ecclesiological perspective. This study employed a qualitative method with a descriptive approach. The subjects were Sunday School children at (insert church name) Church. Data collection was conducted through observation and interviews during environmental education and practices, such as cleaning the church grounds and recycling plastic bottles into plant pots. The data obtained were analyzed descriptively to understand changes in children's attitudes and understanding of environmental awareness. The results showed that the education and hands-on practices enhanced children's understanding of the importance of environmental protection as part of their Christian faith responsibilities. The children demonstrated enthusiasm, active involvement, and an initial awareness of implementing environmentally conscious behaviors in their daily lives. These activities reflect the application of eco-ecclesiology, where faith is demonstrated through concrete actions in caring for God's creation.